Murder, Inc., and the Moral Life : Gangsters and Gangbusters in La Guardia's New York - Whalen, Robert Weldon, 1950- (Book collections on Project MUSE., 2016)
"Murder, Inc. and the Moral Life: Gangsters and Gangbusters in La Guardia's New York tells the story of the notorious 1930s Brooklyn gang nicknamed "Murder, Inc." Murder, Inc. is as well an extended moral reflection on the phenomenon of gangsters in general and the Murder, Inc. gang in particular"--